The semiological and semantic isomorphism in the novels of Bint al-Huda: A semiotic study - Mahoor, Falah Abdul Hassan; Mohsen, Carnvall Ayuob (Al-Adab Journal, 2021)
Narrative semiotics (the Paris school of semiotics), represented by its pioneer and founder, Algirdas Julian Grimas, has been interested in the theme of isotopi with its semiotic and semantic divisions, and explored its role and importance in the process of harmonizing or dissonanting the narrative text, and remove the Ambiguous from it, and how is the Isotopi represents a theory for analyzing the text in all its aspects. This research will study the semiotic Isotopi and semantic Isotopi homogeneity in the novels of the Iraqi writer Bint Al Huda